2020
DOI: 10.1186/s40792-020-01088-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporary spontaneous regression of male breast cancer: a case report

Abstract: Background Spontaneous regression (SR) of a malignant tumor is the partial or complete disappearance of primary or metastatic tumor tissue in the absence of treatment, which can be temporary or permanent. Here, we report an extremely rare case of male breast cancer that exhibited temporary SR followed by reappearance 8 months after tumor disappearance. Case presentation A 70-year-old man presented at our hospital with a primary complaint of pain and a lump in his left breast. Ultrasonography revealed a hypoec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A thorough search in PubMed was performed in order to find all cases of epithelial BC–SR published so far (December 2022). Twenty-nine reported cases were found [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The results of our literature search are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough search in PubMed was performed in order to find all cases of epithelial BC–SR published so far (December 2022). Twenty-nine reported cases were found [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The results of our literature search are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Although breast carcinoma is a common malignancy, cases of SR described in the literature are extremely rare [ 3 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Hundreds of tumor regressions published so far have been reviewed; however, to date, only twenty-nine cases of regressed epithelial breast cancer can be considered reliable [ 3 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. We noticed that most of the patients were female in a wide age range.…”
Section: Discussionmentioning
confidence: 99%
“…[3] In 2020, there was a case report on the recurrence of an estrogen receptor positive breast cancer in a male patient following temporary spontaneous regression. [4] Hormones and endocrine factors have been cited in the literature as a possible cause of spontaneous regression, and with the wellknown influence of hormones in breast cancer, it is possible that the estrogen receptor status of the breast cancer may have an influence on the frequency of spontaneous regression. e American Journal of Clinical Oncology published a review in 1998, which demonstrated a higher prevalence of relapse in estrogen receptor positive breast cancer cases 8 years after mastectomy, as compared to estrogen receptor negative cases.…”
Section: Discussionmentioning
confidence: 99%